Circulating and disseminated tumor cells as a possible prognostic factor for oncological diseases - Andrei D. Kaprin (IP Habib O.N., 2021)
Background. Distant metastasis remains the main cause of death for patients, despite some successes in the diagnosis and treatment of solid tumors. This demonstrates the significance to study the methods for the timely detection of tumor micrometastases and to find the role of tumor cells preserved in peripheral blood or disseminated tumor cells in bone marrow after the end of the treatment.